Cultura organizacional como elemento facilitador na implantação do programa de compliance na área de infraestrutura da Odebrecht Engenharia e Construção - Levorato, Danielle Cristine da Silva (2018)
This applied paper presents a case study on which aspects of the organizational culture can facilitate the implementation of the compliance program in the Infrastructure area of Odebrecht Engineering and Construction, according to Decree nº 8.420/15. The compliance theme is a topic on the agenda in national studies, especially from the operations related to the fight against corruption that were deflagrated in 2014 with Operation Lava Jato. However, the implementation process of the compliance program may vary in organizations with different cultures. The paper was developed from a single case study, with data collection through documents and records in organizational files, related to the culture and the actions of implementation of the compliance system, and public domain documents produced in the year 2017, the year following the signing of the leniency agreement of the company with the Federal Public Ministry, and an in person interview with the compliance coordinator of Odebrecht Engineering and Construction. The data were examined through content analysis with the categorical analysis of the documents. Among the results found, the role of the organizational culture in the implementation of the compliance program in the Infrastructure area of Odebrecht Engineering and Construction stands out; the current culture, widely disseminated to employees through communication and training actions, throughout the company's years, is a variable that can minimize resistance to the implementation of the compliance program, encouraging the collaboration of the members through actions that reinforce the values conveyed in the documents that present Odebrecht culture. This paper has practical implications for Brazilian organizations that are implementing compliance programs, because the issues explored here help to highlight how compliance programs can be structured in accordance with Decree nº 8.420/15 in alignment with the existing organizational culture, seeking the engagement of the members in the implementation process, avoiding resistance from these members. It is a relevant contribution considering the company chosen for the study, which holds a prominent position in the national and international scenarios in the various segments in which it operates, and which was heavily involved in corruption actions. The ongoing compliance program in the organization shows the path of the company's restructuring towards the foundational values proposed by its founder.